The Impact of Tourism Development on Gender Role Transformation and Fisherfolk Welfare in Sanur, Bali - Prastyadewi, Made Ika; Putu Yusi Pramandari (Cita konsultindo, 2026)
Tourism development in Sanur has reshaped the economic and social dynamics of coastal fishing communities. This study analyzes how tourism influences gender role transformation and the welfare of fisher households using a quantitative design with survey data from 120 respondents. Multiple regression results show that tourism significantly contributes to livelihood diversification and increases women’s participation in income-generating activities such as small trading, culinary services, and tourism support services. These changes positively affect household welfare, with livelihood diversification acting as a key mediating factor. However, the shift in gender roles remains limited, as cultural norms continue to restrict women’s involvement in major household decisions. The findings highlight that while tourism enhances economic resilience, it does not automatically create gender equality. Therefore, gender-inclusive policies, training access, and support for women’s entrepreneurial activities are essential to ensure that tourism growth leads to more equitable and sustainable welfare outcomes in coastal communitie.